Lighting up the structure and electronic properties of α-, β-, γ-Ag2WO4 polymorphs under laser irradiation: a DFT investigation - Cabral, L. [UNESP]; Longo, Elson; San-Miguel, Miguel A.; Leite, Edson; da Silva, E. Z.; Andrés, Juan (Royal Society of Chemistry (RSC), 2025)
Laser irradiation (LI)-matter interaction provides a versatile means to manipulate the physicochemical properties of materials. Understanding material responses to LI was the initial driving force for studying the effects of this interaction in solids, but the associated induced dynamics is hindered by the macroscopic number of particles interacting collectively with photonic modes. In this work, we conduct comprehensive theoretical calculations to gain insights into the changes in the lattice structure and electronic properties of α-, β-, γ-Ag2WO4 polymorphs induced by LI using density functional theory (DFT) calculations based on the electronic temperature (Te) within a two-temperature model (TTM) and ab initio molecular dynamics (AIMD) simulations. Overall, we reveal a clear visualization of how Te induces a structural and electronic transformation process during LI. The analysis of the evolution of the pair correlation function confirms that these polymorphs undergo a transition from crystalline to an amorphous structure under strong electronic excitations with concomitant formation of Ag nanoclusters. These results suggest the critical role that the Ag metallic nanoparticles may play in defining the behavior and properties of these materials. Our results offer physical insights into the thermodynamic stability and electronic properties of laser-irradiated Ag2WO4 polymorphs, which can inform on structural details currently inaccessible to experimental techniques. The presented approach is a versatile and sensitive tool for studying defect distribution and clustering processes in other functional Ag-based semiconductors.